IMPLEMENTASI NILAI-NILAI KARAKTER DALAM DONGENG PADA PEMBENTUKAN KARAKTER ANAK DI SDN 11 SANUR - Lastini, Ni Nyoman Ari; anggreni, Ni made (Institut Hindu Dharma Negeri Denpasar, 2017)
Character education is a foundation of a nation that needs to be invested early on to children. Children grow and flourish in a life that is colored by violation of the rights of others to violence, coercion, ignorance, confusion between right and wrong, good and bad, behavior may and may not be done. The inculcation of character education values should start early in the home, community, and school. Character education is expected to make students skilled, knowledgeable, and morals. Students are expected not only to have intellectual ability, more than tuition is also expected to have good character. Good intellectual ability must be balanced with good character education as well. The tale will provide a place for children to learn various emotions and feelings as well as learn the values of the characters.